ANALISYS INFLUENCER MARKETING AND COUNTRY OF ORIGIN IN INCREASING ONLINE PURCHASE INTENTION ON BEAUTY PRODUCT FROM SOUTH KOREA THROUGH PERCEIVED QUALITY - Misa Putri Tanjung; Kokom Komariah; Faizal Mulia Z (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The role of influencers is influential among young people as a creative strategy in marketing beauty products. The spread of promotions through social media makes it easier for users to select the desired product. It is not uncommon for the country of origin label to trigger buying interest with the country's image attached to its consistency in product innovation. However, the intense competition in the Indonesian cosmetic market affects the position of imported cosmetic brands which also affects market share. So that many cosmetic brands are competing to market their products through relevant influencers as an effective and efficient marketing strategy. This study aims to examine the role of perceived quality in mediating influencer marketing and country of origin in increasing online purchase intention among university students in Sukabumi who use beauty products. This research uses quantitative methods with an associative approach. The sampling technique used the Probability samling method using proportional sampling calculation as many as 240 respondents. Data analysis using SEM-PLS with smartPLS 4 software. The results of this study indicate that Influencer Marketing and Country Of Origin have a positive effect on Online Purchase Intention and Perceived Quality has a positive and significant effect in mediating the influence of Influencer Markering and Country Of Origin on Online Purchase Intention.